Political ideologies and identity in British newspaper discourse - Hardman, Dean (2008)
Newspaper editorials have a special role within the pages of the press, as they are openly persuasive and there is less emphasis on objectivity (Lee and Lin, 2006). They represent the participation of the newspaper in public debate (Le, 2003) and are sites where the ideological stances of a newspaper can often be found (Hackett and Zhao, 1994). Editorials frequently focus upon issues surrounding national politics, often discussing political leaders and the decisions taken by leading politicians. This thesis investigates four British newspapers, The Guardian, The Telegraph, the Daily Mail and the Mirror, in order to assess the different ways in which identities have been constructed over the past thirty-five years by the newspapers for the political leaders featured in the editorials. The thesis utilises a novel analytical framework that modifies Critical Discourse Analysis by incorporating theories of performed identities and metaphor with a "Discourse Historical" approach to critical analysis.